2020
DOI: 10.1016/j.actbio.2020.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of controlled dual growth factor delivery on bone regeneration following composite bone-muscle injury

Abstract: Highlights• We developed a smart growth factor delivery system using heparin microparticles and alginate that facilitates tunable delivery of VEGF and BMP-2 in a simultaneous or sequential manner by merely varying the loading strategy.• In vitro, both VEGF and BMP-2 alone promoted vascular growth; however, VEGF was significantly more potent, and there was no detectable benefit of co-delivery.• In vivo, both BMP-2 alone and co-delivery of VEGF and BMP-2 promoted bone formation in the challenging bone/muscle pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…In fact, the effect of additional application of VEGF to BMP-2 on bone healing is discussed controversially in the literature. It has recently been shown that the simultaneous or tunable co-delivery of low-dose BMP-2 and VEGF fails to fully restore the mechanics of bone in a bone defect model ( Subbiah et al, 2020 ). Moreover, Samee et al (2008) found that human periosteum-derived cells transfected with BMP-2 and VEGF in vitro do not show more bone formation at 8 weeks after implantation than human periosteum-derived cells transfected only with BMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the effect of additional application of VEGF to BMP-2 on bone healing is discussed controversially in the literature. It has recently been shown that the simultaneous or tunable co-delivery of low-dose BMP-2 and VEGF fails to fully restore the mechanics of bone in a bone defect model ( Subbiah et al, 2020 ). Moreover, Samee et al (2008) found that human periosteum-derived cells transfected with BMP-2 and VEGF in vitro do not show more bone formation at 8 weeks after implantation than human periosteum-derived cells transfected only with BMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Since many proteins interact with ECM molecules, multiple proteins may interact with the same biomaterial, which may be advantageous for developing strategies to deliver multiple ECM-binding proteins. 84,85 However, the promiscuous binding of heparin and other ECM molecules to a variety of heparin binding proteins can also be disruptive when these biomaterials are delivered in vivo and non-specific, competitive binding to abundant serum proteins can result in accelerated payload release. 86 Thus, caution should be exercised when employing ECM-based biomaterials, which could unintentionally bind additional proteins involved in other cellular processes, resulting in off-target effects and unpredictable protein release in vivo.…”
Section: Reviewmentioning
confidence: 99%
“…However, to achieve optimal bone formation, the coupling of osteogenesis and angiogenesis needs to be deliberately tailored in spatiotemporal manners [ 12 ]. To meet this demand, delivery systems with the ability to simultaneously supply osteogenic and angiogenic growth factors have been developed [ 13 , 14 ]. Unfortunately, current delivery systems do not effectively imitate the pattern by which growth factors appear and act in vivo but act as depots for high concentrations of growth factors.…”
Section: Introductionmentioning
confidence: 99%